Dukungan Orang Tua Terhadap Motivasi Berprestasi Atlet Bulutangkis PB Satria Mandiri Boja (Universitas Negeri Semarang, 2022)
The contribution of parents and close people is a measure of a child's success. The role of parents is very important in supporting children to excel in a sport activity. The focus of the problem in this study is the extent of parental support for fencing athletes in Boja Regency. The purpose of this study was to describe and conclude the effect of parental support on the achievement motivation of badminton athletes at PB Satria Mandiri, Boja, Kendal Regency. This research is quantitative descriptive. The location of the research was carried out in PB Satria Mandiri Boja, Kendal Regency. The data collection technique in this study used a questionnaire method with descriptive data analysis techniques using IBM Statistic 23. This study also used a percentage analysis technique with the formula P = F/N x100. The sample in this study used a total sampling technique. The sample in this study was the athlete of PB Satria Mandiri. This study shows that the component of emotional support (X1) with a total of 2.96 and a percentage of 74% in the good category in supporting their children in participating in badminton, award support (X2) has a total of 2.99 with a percentage of 75% in the good category, then support information X(3) has the highest average value of 3.04 with a percentage of 76% and good category, and the last is instrumental support (X4) which has the lowest average value of 1.4 with a percentage of 44% in the less category to support their children in participating in badminton.